2019
DOI: 10.1111/are.14360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serotonin injection on the reproductive parameters and haemolymph methyl farnesoate level in the narrow‐clawed crayfishPontastacus leptodactylus(Eschscholtz, 1823)

Abstract: The effects of serotonin injection (1, 5 and 10 µg/g body weight) on spermatozoal production, vas deferens index (VDI), hepatosomatic index (HSI), testicular index (TI), gonado‐somatic index (GSI), ovarian egg number, total protein, methyl farnesoate (MF) levels of haemolymph, amino acid and fatty acid profiles of hepatopancreas were evaluated in Pontastacus leptodactylus. In male P. leptodactylus, the highest spermatozoal number (9.3 × 106 ± 1.2) and MF level (0.66 ± 0.06 ng−1 ml) were observed after injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Serotonin seems to increase diameter in oocytes and enhance ovarian maturation in crustaceans (Sarojini et al, 1995; Tinikul et al, 2008). Furthermore, from two studies of narrow‐clawed crayfish (Farhadi et al, 2020) and the crayfish Procambarus clarkii (Sarojini et al, 1995), serotonin was found to act as a stimulator in male reproductive parameters and, more specifically, in testis development.…”
Section: Biological Features—comparison Of the Species Astacus And Po...mentioning
confidence: 99%
“…Serotonin seems to increase diameter in oocytes and enhance ovarian maturation in crustaceans (Sarojini et al, 1995; Tinikul et al, 2008). Furthermore, from two studies of narrow‐clawed crayfish (Farhadi et al, 2020) and the crayfish Procambarus clarkii (Sarojini et al, 1995), serotonin was found to act as a stimulator in male reproductive parameters and, more specifically, in testis development.…”
Section: Biological Features—comparison Of the Species Astacus And Po...mentioning
confidence: 99%
“…A combination of spiperone (a dopamine antagonist) and serotonin was shown to induce ovarian maturation in M. rosenbergii ( 58 ) together with enhanced spawning in L. vannamei and Litopenaeus stylirostris ( 59 ) compared with the injection of serotonin alone. Serotonin also stimulated male reproductive parameters and testis development in the narrow clawed crayfish, Pontastacus leptodactylu s ( 60 ) and the crayfish P. clarkii ( 61 ).…”
Section: Serotoninmentioning
confidence: 99%
“…The narrow‐clawed crayfish ( Pontastacus leptodactylus ) is widely distributed from Iran in the east and south, the Czech Republic in the west, and Russia in the north (Farhadi, Harlıoğlu, & Gür, 2019; Harlıoğlu et al, 2012; Harlıoğlu & Duran, 2010; Niksirat et al, 2015). There is a great interest in the culture of P. leptodactylus due to its delicious taste and high price (Farhadi, Harlıoğlu, & Yılmaz, 2019; Niksirat et al, 2014). However, the sustainable development of the freshwater crayfish industry suffers from several diseases caused by infectious pathogens, including viruses (Sakuna et al, 2018), bacteria (Davidovich et al, 2019), and fungi (Kokko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%